2010
DOI: 10.1021/ja106653a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Tuning of Molecular Recognition To Discriminate the Single-Methyl-Group Difference between Thymine and Uracil

Abstract: Construction of enzyme-like artificial cavities is a complex and challenging subject. Rather than synthesizing complicated host molecules, we have proposed mechanical adaptation of relatively simple hosts within dynamic media to determine the optimum conformation for molecular recognition. Here we have applied this concept to one of the most challenging biomolecular recognition problems, i.e., that of discriminating thymine from uracil. We synthesized the novel cholesterol-armed triazacyclononane as a host mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 53 publications
2
82
0
3
Order By: Relevance
“…These changes in area were obtained from the difference between neat monolayers and monolayers spread on subphases containing 0.05 mg mL −1 derivatives at a fixed pressure of 30 mN m −1 . The larger expansion for DPPCT is consistent with the results by Mori et al [37], where an additional CH 3 group in thymine -compared to uracyl -yielded a larger expansion of cholesterol-armed triazacylclononane monolayers. Since area was larger for the zwitterionic DPPC for DPPCT subphases and the same as for DPPG and DMPA for DACT subphases, one infers that electrostatic interactions cannot be the dominant force.…”
Section: Resultssupporting
confidence: 90%
“…These changes in area were obtained from the difference between neat monolayers and monolayers spread on subphases containing 0.05 mg mL −1 derivatives at a fixed pressure of 30 mN m −1 . The larger expansion for DPPCT is consistent with the results by Mori et al [37], where an additional CH 3 group in thymine -compared to uracyl -yielded a larger expansion of cholesterol-armed triazacylclononane monolayers. Since area was larger for the zwitterionic DPPC for DPPCT subphases and the same as for DPPG and DMPA for DACT subphases, one infers that electrostatic interactions cannot be the dominant force.…”
Section: Resultssupporting
confidence: 90%
“…The molecular machine can catch and release guest molecules based on hand-motion-like microscopic motions. Similarly, control of molecular phenomena including chiral recognition [48,49], nucleic acid base discrimination [50], glucose detection by indicator displacement assay [51], and controllable drug delivery [52] by macroscopic mechanical motions have been demonstrated using interfacial media and related structures. These are realistic examples of accessing molecular-level functions from the macroscopic world.…”
Section: Future Approaches For Access From Macro To Moleculementioning
confidence: 99%
“…[20] Recently,w eh ave reported that molecular properties can be tuned by applying amechanical force to amonolayer at the air-water interface. [21][22][23] However,a lthough variation of properties should originate from changes at the molecular level, at that time these could be only inferred.…”
mentioning
confidence: 99%